An introduction to Concepts of Justice in Islam - Kashani, Mohammad Reza Akhzarian (Advances in Social Sciences Research Journal, 2018)
Conceptual justice is so broad that, at the same time, apparent simplicity is associated with many complications, and thinkers, philosophers, economists, and lawyers ... have more than two thousand years ago still sought to find the right meaning.The concept of justice is understandable and desirable for most human societies, and this utility and importance for Muslims has been doubled. One of the ideological questions and ideals of Islamic thought was the concept of justice, which had a high status in Islamic thought and undeniable role among the Shi’ites as one of the largest Muslim groups. This paper seeks to clarify, at the same time, a comprehensive and thorough explanation of their idealistic approach to justice by examining the most important principles and concepts of justice from the Muslim perspective. On this basis, justice is considered from a number of perspectives, and the approach of the Quran as the main source of Muslims, as well as the approach of Muslim theologians and Muslim jurists.